A Spatial Assessment of Wildfire Risk for Transmission-Line Corridor Based on a Weighted Naïve Bayes Model - Xiang, Kunxuan; Zhou, You; Zhou, Enze; Lu, Junhan; Liu, Hui; Huang, Yu (Frontiers in Energy Research, 2022)
In order to improve the wildfire prevention capacity of transmission-lines, a wildfire risk assessment method of transmission-line corridors based on Weighted Naïve Bayes (WNB) is proposed in this paper. Firstly, the importance of collected 14 types of wildfire-related factors is analysed based on the information gain ratio. Then, the optimal factors set and the most accurate sampling table are constructed by deleting the factors in the lowest order of importance one by one. Finally, performance of the WNB model is compared to that of NB and BNW models according to the ROC curve and visualization. 76.36% of fire events in 2020 falls in high-risk and very-high-risk regions indicating the acceptable accuracy of the proposed assessment method of wildfire risk.